Directors tenure diversity and corporate sustainability performance: The non-linear evidence from Indonesia public listed companies - Ardianto, Ardianto; Cahyono, Suham; Harymawan, Iman (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2024)
The primary objective of this study is to thoroughly investigate the association between director tenure diversity and corporate sustainability performance. This study utilizes a sample comprising 578 firm-year observations from non-financial companies listed on the Indonesia Stock Exchange. To test the hypothesis, the study employs the Ordinary Least Squares method, complemented by a series of endogeneity tests. This study reveals that the sustainability performance of corporations in Indonesia falls significantly short of satisfactory levels. Furthermore, the study indicates that there is a negative association between tenure diversity and sustainability performance, demonstrating a U-shaped curve pattern. To ensure the robustness of our findings, we performed additional analysis using coarsened exact matching and Heckman (1979) two-stage least square methodologies, confirming that the results remained consistent with those of the initial test. Intriguingly, our supplementary analyses also revealed an inverse association between tenure diversity in the boardroom and sustainability performance within companies. This study makes a significant contribution to the corporate governance literature by elucidating the inverse association between director tenure diversity and sustainability performance. In doing so, it enhances the originality and novelty of existing studies, particularly within the context of developing countries, such as Indonesia. This study exhibits novelty by embracing a quantitative approach to measure sustainability performance, revealing an intriguing inverse association between sustainability performance and ESG initiatives within the companies.